Manajemen Kualitas dalam Meningkatkan Efisiensi Proses Bisnis Perusahaan - Safuan Safuan; Rini Rini; Dea Maulidta; Valenthreeas Hijriyana; Fatemma Azzahra (Jurnal Syntax Admiration, 2024)
In an era of increasingly fierce business competition, companies are required to improve efficiency in every business process. One of the crucial aspects that can support efficiency is the implementation of proper quality management. Quality management is a systematic approach to managing and improving the quality of products, services, and processes in an organization, with the goal of meeting customer expectations and achieving optimal efficiency. This research explores various quality management approaches such as Total Quality Management (TQM), Six Sigma, Lean Manufacturing, and ISO 9001. This approach has a focus on continuous improvement, elimination of waste, and increased customer satisfaction. This study uses a qualitative descriptive method to analyze the implementation of these models in improving the efficiency of the company's business processes. The results of the assessment from the media expert, Mr. Muhammad Ikhwan, S.Pd., M.Pd showed the feasibility of the media with an average score of 92.17%, while the assessment of the material expert, Mrs. Nurul Isnaeni, S.Pd, obtained an average of 96.19%, with the category of "Very Feasible" for all aspects. This study proves that Powtoon-based learning media is effective and feasible to use in the context of education.